(untitled) - Felch, Ginny (Wiley, 2011)
Family photography continues to be a major field of professional digital photography, while amateur moms are the fastest growing segment of digital camera owners. No matter your level of expertise, you’ll benefit from the invaluable advice featured in this new edition. Updated with new photos and revised text to cover the latest technologies, this inspirational book offers critical assistance with photographing children in portrait or candid situations, natural environments or structured interiors, and any variety of lighting. You’ll find practical techniques as well as artistic guidance to capture a photo that radiates the innocence and magic of childhood.
Keywords: Photography of children; Nhiếp ảnh trẻ em